The MAGEEQ project: identifying contesting meanings of «gender equality» - Bacchi, Carol (The Greek Review of Social Research, 2016)
In this article I engage with MAGEEQ methodology and theoretical assumptions to raise questions around the following themes: intentionality in political practice, meanings of discourse, and understandings of political subjectivity. I make the case that these topics need to be addressed in order to provide insights into the reasons social change is so difficult to achieve. Specifically, I suggest that feminists adopt a practice of «reflexive framing», examining how they represent social «problems», and broaden feminist constituencies through coalition to reduce the possibility of representing «problems» in ways that exclude or harm «others».